Higher cord blood 25-hydroxyvitamin D concentrations reduce the risk of early childhood eczema: in children with a family history of allergic disease. Issue 1 (December 2015) - Palmer, Debra; Sullivan, Thomas; Skeaff, Clark; Smithers, Lisa; Makrides, Maria
Abstract Background In recent years the role of vitamin D status in early life on the development of allergic disease has generated much interest. The aim of this study was to determine whether cord blood vitamin D concentrations were associated with risk of early childhood allergic disease. Methods Measurements of cord blood 25-hydroxyvitamin D [25(OH)D] concentrations were available in 270 mother-child pairs who were participating in the allergy follow-up (n  = 706) of the Docosahexaenoic Acid to Optimise Mother Infant Outcome randomised controlled trial. All of the children had a hereditary risk of allergic disease. The diagnosis of allergic disease was made during medical assessments at 1 and 3 years of age. Results The mean (standard deviation) standardised cord blood 25(OH)D concentration was 57.0 (24.1) nmol/L. The cumulative incidence of eczema to 3 years of age, n  = 101/250 (40 %) was associated with standardised cord blood 25(OH)D concentration, with a 10 nmol/L rise in 25(OH)D concentration reducing the risk of eczema by 8 % (relative risk 0.92, 95 % confidence interval 0.86–0.97;P  = 0.005). This association was stronger at 1 year of age, when a 10 nmol/L rise in standardised cord blood 25(OH)D concentration reduced the risk of eczema by 12 % (relative risk 0.88, 95 % confidence interval 0.81–0.96;P  = 0.002). No associations between cord blood 25(OH)D concentrations and development of allergic sensitisation, allergic rhinitis or asthma in early childhood were found. Conclusion In children with a family history of allergic disease, a higher cord blood 25(OH)D concentration appears to be associated with reduced risk of eczema in early childhood. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12610000735055 (DOMInO trial:ACTRN12605000569606 ).